Global Business Cycles : Convergence or Decoupling? - Kose, Ayhan; Otrok, Christopher; Prasad, Eswar (Washington, D.C. : International Monetary Fund, 2008)
This paper analyzes the evolution of the degree of global cyclical interdependence over the period 1960-2005. We categorize the 106 countries in our sample into three groups-industrial countries, emerging markets, and other developing economies. Using a dynamic factor model, we then decompose macroeconomic fluctuations in key macroeconomic aggregates-output, consumption, and investment-into different factors. These are: (i) a global factor, which picks up fluctuations that are common across all variables and countries; (ii) three group-specific factors, which capture fluctuations that are common to all variables and all countries within each group of countries; (iii) country factors, which are common across all aggregates in a given country; and (iv) idiosyncratic factors specific to each time series. Our main result is that, during the period of globalization (1985-2005), there has been some convergence of business cycle fluctuations among the group of industrial economies and among the group of emerging market economies. Surprisingly, there has been a concomitant decline in the relative importance of the global factor. In other words, there is evidence of business cycle convergence within each of these two groups of countries but divergence (or decoupling) between them.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet